EXPLORING THE PRETABILITY POTENTIAL OF TRITICALE CULTIVATION IN THE LĂPUȘ DEPRESSION, ROMANIA: A SCIENTIFIC ANALYSIS - Iuliana Cionca; Giorgiana-Alina Spaller; Alexandru-Daniel Costin; Teodor Rusu (Agricultura)
Two factors were studied between the years 2021-2022 and 2022-2023 in Jugăstreni, Vima Mică common, Maramureș County, in the Lăpuș Depression, Romania: fertilizers and herbicides and their impact at production of triticale crop. Before applying anything, a soil profile was realized to find out the type of the soil, quality class and credit points. The soil type is typical luvosol, the quality class of the soil is II, with 64 evaluation points. For the fertilizers the production was monitored and for the herbicides the frequency and resistance of the weeds. Four variants of fertilizers were administrated in four repetitions and also three variants of herbicides, having one variant without any herbicide as a comparison. The productions obtained were 7469.75 kg/ha for the first fertilization option and 9047 for the 4th fertilization option. During the growth stages of triticale, the observations about weeds and plants were made and data collected. The quantities of fertilizers were established after the first soil analysis made at OSPA Cluj-Napoca, and the herbicides were chose considering the area and what is mostly used by the farmers and depending on what type of weeds appear frequently in triticale crop.